2018
DOI: 10.3892/ijmm.2018.3993
|View full text |Cite
|
Sign up to set email alerts
|

Isorhamnetin alleviates lipopolysaccharide-induced inflammatory responses in BV2 microglia by inactivating NF-κB, blocking the TLR4 pathway and reducing ROS generation

Abstract: Isorhamnetin, which is a flavonoid predominantly found in fruits and leaves of various plants, including Hippophae rhamnoides L. and Oenanthe javanica (Blume) DC, is known to possess various pharmacological effects. However, the anti-inflammatory potential of isorhamnetin remains poorly studied. Therefore, the present study aimed to investigate the inhibitory potential of isorhamnetin against inflammatory responses in lipopolysaccharide (LPS)-stimulated BV2 microglia. To measure the effects of isorhamnetin on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 39 publications
6
49
0
Order By: Relevance
“…It should be noted that the inhibition of the iNOS signaling pathway would also influence the NO production. LPS is an iNOS inducer that increases NO concentrations, through the activation of inducible nuclear factors, including NF‐κβ, so its inhibition would lead to a decrease in NO concentration (Kim et al, 2019), response was also observed in F1–3 kDa of the present study.…”
Section: Resultssupporting
confidence: 73%
“…It should be noted that the inhibition of the iNOS signaling pathway would also influence the NO production. LPS is an iNOS inducer that increases NO concentrations, through the activation of inducible nuclear factors, including NF‐κβ, so its inhibition would lead to a decrease in NO concentration (Kim et al, 2019), response was also observed in F1–3 kDa of the present study.…”
Section: Resultssupporting
confidence: 73%
“…A previous study has found that a plantar injection of CFA could induce mechanical allodynia via microglial activation and induction of pro-inflammatory cytokines in the spinal cord [20,23,26]. In this study, the oral administration of EJE attenuated CFA-induced mechanical allodynia, microglial activation, and the expression of pro-inflammatory cytokines in the spinal cord.…”
Section: Discussionsupporting
confidence: 58%
“…We next investigated the mechanisms underlying the suppressive effect of EJE in LPS-induced microglial activation. Over the course of microglial activation, the MAPK signaling pathway is activated to induce inflammation and the expression of pro-inflammatory cytokines [25,26]. In our data, LPS treatment induced the activation of the MAPK pathways in BV2 microglia.…”
Section: Discussionsupporting
confidence: 52%
“…TLR4/MyD88-dependent signaling recruits IRAK1/TRAF6 complex, leading to TAK1 phosphorylation and subsequently activates NF-κB and MAPKs by phosphorylating IκBα and MAPK signaling pathways [ 39 , 41 ]. TLR4, MyD88, and TRAF6 are weakly expressed by resting cells, but they upregulate following stimulation with LPS [ 42 ]. In our study, although Hp-s1 pretreatment did not affect TLR4 expression, Hp-s1 attenuated LPS-induced the increase in the expression of MyD88 and TRAF6, which contributes to suppressing proinflammatory responses.…”
Section: Discussionmentioning
confidence: 99%